2017
DOI: 10.1097/bot.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Misuse of Opioids in Orthopaedic Postoperative Patients

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Half of their patients required opioid medication for only 2 days after the surgical procedure. Investigations in the orthopaedic trauma literature have highlighted the importance of socioeconomic status in predicting postoperative opioid consumption, with unemployed, lowerincome, and less-educated patients more likely to believe that they were underprescribed pain medication and seek additional opioid medication beyond that prescribed by their surgeon 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of their patients required opioid medication for only 2 days after the surgical procedure. Investigations in the orthopaedic trauma literature have highlighted the importance of socioeconomic status in predicting postoperative opioid consumption, with unemployed, lowerincome, and less-educated patients more likely to believe that they were underprescribed pain medication and seek additional opioid medication beyond that prescribed by their surgeon 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The selection bias involving patients who agreed to study participation may have influenced our results if these patients differed systematically from those who declined enrollment. Additionally, our suburban study location resulted in few underinsured or low-socioeconomic-status patients being enrolled, which is a group known to require higher levels of opioids after orthopaedic procedures 18,19 . Some surgical variability may have occurred within our procedure groupings for which we were unable to account.…”
Section: Discussionmentioning
confidence: 99%
“…Prior opioid use has been shown to be associated with adverse clinical outcomes in surgical and trauma patients including higher pain, greater rates of postoperative morbidity, and lower levels of satisfaction. [1][2][3] Opioid exposure in the context of a traumatic injury may also increase the potential for dependence, misuse, and abuse. [1][2][3] A history of prescription opioid abuse is a significant risk factor for conversion to heroin use.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Opioid exposure in the context of a traumatic injury may also increase the potential for dependence, misuse, and abuse. [1][2][3] A history of prescription opioid abuse is a significant risk factor for conversion to heroin use. 4 The potential for these adverse events may be even higher among patients who sustain trauma to the musculoskeletal system, a group previously found to have elevated rates of chemical dependence, risk-taking behavior, concomitant behavioral health disorders, and other sociodemographic characteristics associated with opioid abuse such as underemployment and lower socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…Given the recent trend in the abuse of prescription of opioids, a study examined identifying patterns of postoperative opioid misuse among patients with orthopaedic trauma 24 . The results of the survey completed by 182 patients revealed that 19.2% of patients felt undermedicated, 12.6% admitted to using pain medications at a higher dose than prescribed, and 9.3% admitted to using external opioids.…”
Section: Opioid Usementioning
confidence: 99%